Low-Carbon Pathways in Solid Waste Management: A Systematic Review of Carbon Footprint and GHG Mitigation across Technologies and Regions - Safira Putri H. Malik; Fitryane Lihawa; Dewi Wahyuni K. Baderan (West Science Interdisciplinary Studies, 2025)
Carbon footprinting and greenhouse gas (GHG) accounting are now widely applied to solid waste management (SWM), yet evidence remains fragmented across technologies, waste streams, and regional contexts. This systematic literature review synthesizes 50 Scopus-indexed journal articles (2017–2025) that quantify the carbon outcomes of SWM options using life-cycle assessment, carbon accounting, and sce-nario modeling. We compare methodological choices (functional units, boundaries, impact methods, avoided burdens), benchmark core treatment technologies (landfilling, incineration/WtE, composting, anaerobic digestion, mechanical-biological treatment), assess circular pathways (recycling, substitution, eco-design), and identify regionally differentiated transition archetypes shaped by governance and ener-gy-system decarbonization. Across studies, technology rankings are highly sensitive to methane dynamics, landfill gas capture and oxidation, grid emission factors, and substitution assumptions. Circular strategies frequently deliver the largest net savings when high-quality sorting and credible displacement of virgin production are achieved, while WtE benefits are context-dependent and generally increase in fossil-intensive grids. The review proposes an integrative comparison framework that links method choices to technology performance and regional pathway feasibility, providing more comparable, decision-relevant evidence for low-carbon SWM planning.